The Path to Bucha: Organisational Practices of the Russian Army and Violence against Noncombatants - Tomáš Kučera (Vojenské rozhledy, 2022)
The Bucha massacre raises the question of whether the Russian army predisposes its soldiers to unlawful violence against civilians. This article assumes that regardless of superior orders, perpetrators of violence must overcome the psychological barriers developed during socialisation. The psychological mechanism of "moral disengagement" allows soldiers to kill in combat and act violently on civilians. The duty of the armed forces is not only to prepare soldiers to fight and kill but also to prevent illegal violence. The case of the Russian army demonstrates how formal activities to prevent moral disengagement and violations of the International Humanitarian Law (IHL) face insurmountable obstacles in the form of institutional culture and insufficient human capital.